Deconstruction of the Planning Process in the 21st Century - Zali, Nader (European Spatial Research and Policy, 2014)
By increasing the changes in the last years of the second millennium, relying on the planning methods, which are based on forecasting, cannot meet the needs of management of countries at large scale. The heavy burden of uncertainties and emergence of interrupted and wild card events have changed the conditions in a way that future forecasting is not possible for planners. On the other hand, in regional and urban planning it is necessary to change the attitude from forecasting to foresight. Considering this, the paper attempts to introduce the approach of foresight as well as having a critical view of the current process of planning in foreseeing and future studies. Moreover, this study emphasizes the necessity of employing the foresight approach in the process of urban and regional studies.